Visual LISP : a guide to artful programming - Kreiker, Phil. (Albany, NY : Autodesk Press, 2000)
Installing the artful programming API... Manipulating the AutoCAD user. Managing dialog boxes. Manipulating autoCAD drawings with activex automation. Making the most of activex automation. Introduction to reactors. Building and deploying applications.
Keywords: Computer program language; Visual LISP; Visual LISP (Computer program language)